Aislamiento y caracterización de una polifenoloxidasa relacionada con la tolerancia del clavel (Dianthus caryophyllus) a Fusarium oxysporum f. sp. dianthi raza 2 - Roquesa Mayorga, Viana; Higuera M., Blanca Ligia (Acta Biológica Colombiana, 2007)
Polyphenoloxidase (PPO) was isolated and purified from stems of carnation (Dianthus caryophyllus L) after the inoculation with Fusarium oxysporum f. sp. dianthi race 2 (FOD2) of a tolerant variety. Purification was performed using column chromatography of ionic exchange, hydrophobic interaction and molecular exclusion. With these successive steps, a factor of 314 fold purification was achieved. The SDS-PAGE analysis showed one band of 40 kDa. The purified enzyme was partially characterized using cathecol as substrate and determined the optimal temperature as 45ºC and 7.5 as optimal pH. The enzyme showed a Michaelis-Menten kinetic with Km of 249 mM and Vmax 322 U/min. The IP was 5.0 indicating the acidic character of this protein. Using the purified enzyme and its reaction products, in vitro fungitoxic assays were realized indicating an important inhibitory activity against FOD2 of 57% at 24 hours. Then, it is possible to postulate that this enzyme is activated as a part of the defense mechanismsin this interaction model.